KONSEP DIRI DAN MOTIVASI BELAJAR SISWA BROKEN HOME SERTA IMPLIKASINYA DALAM BIMBINGAN DAN KONSELING - Emeliya Hardi (Universitas Muhammadiyah Tapanuli Selatan, 2016)
The purpose of this research was aimed at describing the self-concept and learning motivation of the students growing in a broken home family. In addition, the correlation between learning motivation and self-concept of the broken home students was also tested. This was a descriptive correlational research which used quantitative method. This research was conducted to the students in class X, XI and XII of SMA Pertiwi 1 in academic year 2013/2014. The data of the research was collected through closed-ended questionnaire which applied Likert scale model. The data gained was analyzed by using percentage technique. The result of the research indicated that: (1) the level of the respondent’ response on the self-concept of the broken home students was 76,3% or on medium level, (2) the level of the respondent’ response on the learning motivation of the broken home students was 70% or on medium level, (3) the coefficient correlation of the self-concept and learning motivation of the broken home students was 0,572 signifying that there was a significant correlation between selfconcept and learning motivation of the broken home students